2007
DOI: 10.1103/physrevlett.99.217204
|View full text |Cite
|
Sign up to set email alerts
|

Subpicosecond Magnetization Reversal across Ferrimagnetic Compensation Points

Abstract: Subpicosecond magnetization reversal is experimentally demonstrated by ultrafast heating of a ferrimagnet across its compensation points, under an applied magnetic field. While the reversal is initiated by crossing the magnetization compensation temperature, the short reversal time is related to the angular momentum compensation, where the dynamics of the system is highly accelerated owing to the divergence of the gyromagnetic ratio. These results demonstrate the feasibility of subpicosecond magnetization reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
471
2
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 449 publications
(491 citation statements)
references
References 28 publications
12
471
2
6
Order By: Relevance
“…The fastest precessional reversal demonstrated experimentally using an external magnetic field 2,3 is ∼100 ps, with similar reversal times achieved using a spin-polarized current. [4][5][6] Recent experimental work in the field of magneto-optics has demonstrated that carefully shaped laser pulses can be used to manipulate the magnetization dynamics on the subpicosecond time scale [7][8][9][10][11][12] in many materials, including cobalt, iron, nickel, and GdFeCo. However, controllable magnetization switching has only been observed in GdFeCo, and this has stimulated a great deal of effort to attempt on many levels to explain the process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fastest precessional reversal demonstrated experimentally using an external magnetic field 2,3 is ∼100 ps, with similar reversal times achieved using a spin-polarized current. [4][5][6] Recent experimental work in the field of magneto-optics has demonstrated that carefully shaped laser pulses can be used to manipulate the magnetization dynamics on the subpicosecond time scale [7][8][9][10][11][12] in many materials, including cobalt, iron, nickel, and GdFeCo. However, controllable magnetization switching has only been observed in GdFeCo, and this has stimulated a great deal of effort to attempt on many levels to explain the process.…”
Section: Introductionmentioning
confidence: 99%
“…The excitement for these materials has recovered in the past few years with the observation of ultrafast magnetization switching using femtosecond laser pulses. 10 The atomistic model is currently the only model that can describe ultrafast magnetic processes associated with these types of ferrimagnets, however, to the best of our knowledge, the atomistic model has not yet been applied to such disordered ferrimagnets.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we performed experiments on sample Gd 24 FeCo (black down triangles in Fig.2 at T > T M where no transition through T M was possible due to laser heating. This means that field induced switching scenarios due to crossing of T M can be discarded 34 . Fig.3 shows the fluence dependence of the magnetization evolution in Gd 24 FeCo at T = 300 K and for ∆t = 55 fs.…”
mentioning
confidence: 99%
“…In recent years, owing to an increased interest in ferrimagnetic materials, there have been a number of studies of ultrafast magnetic switching based on increasing the temperature of a ferrimagnetic material over its magnetic compensation point with the help of a short laser pulse [6][7][8] . These studies demonstrated a strongly increased magnetic susceptibility followed by thermally assisted magnetization reversal in an external magnetic field.…”
mentioning
confidence: 99%